La sociedad de consumo, ¿vehículo de progreso o desvío peligroso? - Ramos Gorostiza, José Luis (Iberian Journal of the History of Economic Thought, 2026)
COLLANTES, Fernando, Consumer Society and the Economists. Consumption and Well-Being in the History of Economic Thought, Palgrave Macmillan, 2025. ISBN 3031966449.